The Role of Islamic Bank MSME Financing for Job Creation in Indonesia - Setiawan, Iwan; Tripuspitorini, Fifi Afiyanti; Ruhana, Nafisah; Yanti, Teti Sofia (Jurusan Akuntansi Politeknik Negeri Bandung, 2024)
Population growth has an impact on increasing unemployment due to the limited job opportunities available in Indonesia. The solution to overcoming unemployment is carried out through the development of labor-intensive economic sectors. The micro, small and medium enterprise (MSME) sector has the potential to create jobs. However, the development of MSMEs is hampered by limited sources of funds that can be accessed from financial institutions (banks). The Islamic bank financing system is in accordance with the characteristics of MSMEs, has the potential to encourage increased business and employment for MSMEs. This research aims to examine the impact of Islamic bank financing for MSMEs on job creation in Indonesia. The research was carried out using a multiple regression analysis model with the Ordinary Least Square (OLS) estimation method, using time series data for the monthly period 2016-2023. The research results show that Islamic bank financing in the MSME sector has a significant positive effect on job creation. Every increase in sharia bank financing in the MSME sector provides a direct contribution to job creation. Job creation is also significantly influenced by third party funds from Islamic banks, monetary policy, minimum wage policy, unemployment and economic growth. Increases in third party funds, minimum wages and economic growth have a significant effect on job creation. Increasing monetary policy interest rates and unemployment result in a decrease in job creation.